Nonsequential Response in Mountainous Areas of Southwest China - Liu, Lin; Ye, Sheng; Chen, Cangyi; Pan, Hailong; Ran, Qihua (Frontiers in Earth Science, 2021)
Nonsequential response is the phenomenon where the change of soil water content at the lower layer is larger than that of the upper layer within a set time interval. It is often ignored because of the lack of spatially distributed measurements at the watershed scale, especially in mountainous areas where extensive monitoring network is expensive and difficult to deploy. In this study, the subsurface nonsequential response in a mountainous watershed in Southwest China was investigated by combining field monitoring and numerical simulation. A physics-based numerical model (InHM) was employed to simulate the soil water movement to explore the occurrence of the subsurface nonsequential response. The topographic wetness index [TWI = ln (a/tan b)] was used to distinguish the topographic zone corresponding to the nonsequential response at different depths. The nonsequential response mainly came from the subsurface lateral flow initiated at the soil–bedrock interface or at a relatively impermeable layer. The results showed that the occurrence depth of the nonsequential response increased with precipitation intensity when the time since last event was more than 24 h and the total amount of this event exceeded 37 mm. During a rainfall event, the nonsequential response occurred at the middle layer in the hillslope zone and the deep soil layer beneath the channel. In case of a rainfall event with two peaks, the region observed with nonsequential response expanded. The soil layer at the interface of the bedrock could be saturated quickly, and became saturated upward. This kind of nonsequential response can be observed on the hillslope at the beginning of rainfall events, and then found beneath stream channels afterward. Furthermore, nonsequential response could also happen after rainfall events. The results improved our understanding of nonsequential response and provided a scientific basis for flash flood research in mountainous areas.